Pathologic evidence of pseudoexfoliation in cases of in‐the‐bag intraocular lens subluxation or dislocation. Issue 5 (May 2015) - Liu, Erica; Cole, Scott; Werner, Liliana; Hengerer, Fritz; Mamalis, Nick; Kohnen, Thomas
Abstract : Purpose : To provide complete histopathologic evaluation of explanted capsular bags that spontaneously dislocated in the late postoperative period, with the main objective being to assess the presence of pseudoexfoliation (PXF) material. Setting : Goethe‐University Frankfurt, Frankfurt, Germany, and John A. Moran Eye Center, University of Utah, Salt Lake City, Utah, USA. Design : Retrospective case series. Methods : Standard gross and light microscopy and complete histopathology were performed on explanted subluxated and dislocated capsular bags containing an intraocular lens (IOL) or a capsular tension ring (CTR) and an IOL. Questionnaires were sent to explanting surgeons, and a patient chart review was performed, when available. Results : The specimens were represented by capsular bags containing an IOL (n = 37) or an IOL–CTR (n = 3). The IOLs included 3‐piece hydrophobic acrylic (n = 13), 1‐piece hydrophobic acrylic (n = 7), 3‐piece silicone (n = 6), 1‐piece hydrophilic acrylic (n = 6), 3‐piece hydrophilic acrylic (n = 2), and 1‐piece poly(methyl methacrylate) (PMMA) (n = 6) designs; all CTRs were PMMA. Soemmering ring formation was mild in 8 specimens, moderate in 18 specimens, and severe in 14 specimens. Excessive contraction of the capsular bag with capsulorhexis phimosis was observed in 24 specimens. Twenty‐six specimens had histopathologic evidence of PXF; 13 had a clinical history or evidence of PXF. Conclusions : Pseudoexfoliation might be implicated in a larger proportion of late in‐the‐bag IOL subluxations and dislocations than previously thought as a result of significant clinical underdiagnosis. This might indicate a need for new considerations during the preoperative and postoperative cataract surgery assessments and follow‐up. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.